TRANSNATIONALIZATION AS TOURIST MARKET TREND: HISTORICAL FORMS AND CONTEMPORARY BRANCH SPECIFITY - Victoria S. SALAMATINA (Advanced Engineering Research, 2010)
Transnationalization features in the production and distribution sector of travel services are considered. Historical forms of multinational corporations (MNC) tourism, their organizational structure and economic performance specifity are determined. A modern definition of transnationalization as a trend of world tourism market development is given.